2016
DOI: 10.11152/mu.2013.2066.181.dop
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of fetal Doppler evaluation in early versus late onset intrauterine growth restriction. Review of the literature.

Abstract: Intrauterine growth restriction (IUGR) represents a serious condition that can lead to increased perinatal morbidity, mortality and postnatal impaired neurodevelopment. There are two distinct phenotypes of IUGR: early onset and late onset IUGR with different onset, patterns of evolution and fetal Doppler profile. In early onset preeclampsia the main Doppler modifications are at the level of umbilical artery, with progressive augmentation of the pulsatility index to absent or reverse end diastolic flow. The mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 45 publications
0
75
0
2
Order By: Relevance
“…FGR is divided into early‐onset and late‐onset based on different pathological mechanisms . The pathological basis of early‐onset FGR is the reduction of the villous vascular area and impaired trophoblastic invasion, resulting in massive lesions of the placenta . However, late‐onset FGR could be diffusion failure from placental maladaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGR is divided into early‐onset and late‐onset based on different pathological mechanisms . The pathological basis of early‐onset FGR is the reduction of the villous vascular area and impaired trophoblastic invasion, resulting in massive lesions of the placenta . However, late‐onset FGR could be diffusion failure from placental maladaptation.…”
Section: Discussionmentioning
confidence: 99%
“…13 The pathological basis of early-onset FGR is the reduction of the villous vascular area and impaired trophoblastic invasion, resulting in massive lesions of the placenta. 22,23 However, late-onset FGR could be diffusion failure from placental maladaptation. Early-onset FGR is more severe condition; as shown in our study, perinatal morbidity and mortality rates of early-onset FGR were significantly higher than that of late-onset FGR.…”
Section: Discussionmentioning
confidence: 99%
“…Early-onset preeclampsia is characterized by a high frequency of placental maternal vascular lesions of underperfusion and a small placenta [9094], abnormal umbilical artery and uterine arteries Doppler velocimetry [99104], an abnormal angiogenic/anti-angiogenic profile [58,59,72,80,109,111], fetal growth restriction [9598], and a relatively high rate of thrombocytopenia, elevated liver enzyme abnormalities, and the HELLP syndrome [150]. By contrast, late-onset preeclampsia is thought to result from a mismatch between the nutrient supply by the mother and the metabolic demands of the fetus at the end of pregnancy [7779].…”
Section: Discussionmentioning
confidence: 99%
“…Early-onset preeclampsia is likely caused by a disorder of deep placentation in which there is a failure of physiologic transformation of the spiral arteries, a small placenta with histologic features of maternal vascular underperfusion [9094], fetal growth restriction or small for gestational age [9598], and abnormal Doppler velocimetry of umbilical and uterine arteries [99104]; it frequently requires preterm delivery for maternal and/or fetal indications [12]. By contrast, late-onset preeclampsia seems to be the manifestation of a mismatch between the metabolic demands of the growing fetus close to term and maternal supply [7779]: the placenta has fewer lesions of maternal vascular underperfusion [9093] and abnormalities of umbilical/uterine artery Doppler velocimetry [79].…”
Section: Introductionmentioning
confidence: 99%
“…1 Although systematic and expert reviews of the available literature have shown CPR to be a good predictor of fetal distress in labour, as well as low arterial pH, neonatal intensive care unit (NICU) admissions and poor neonatal morbidity and mortality, it is not yet in regular clinical use. [2][3][4] Calculation of the CPR Cerebro-placental ratio is the ratio that quantifies the brainsparing effects seen in placental insufficiency. It is calculated by dividing the middle cerebral artery (MCA) Doppler flow by the umbilical artery (UA) Doppler flow.…”
mentioning
confidence: 99%